PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN PERTUMBUHAN ASET TERHADAP NILAI PERUSAHAAN - Winarti, Yulita Ayu; Handayani, Nur (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2024)
This Research aimed to examise the effect of capital structure, firm size, and asset growth on firm value. Those three variables were the factors that affected the firm value and further influenced investors’ intention to invest their capital within companies. Moreover, the Capital structure was calculated by Debt to Equity Ratio (DER), firm size was calculated by Firm Size, and assets growth was calculated by assets growth formula. The Research was quantitative. Furthermore, the population was Telecomunication companies listed on the Indonesia Stock Exchange (IDX). The data collection technique used purposive sampling, in which the sample was based on the criteria given. In line with that, there were 16 companies as the sample. Additionally, the observation period was 4 years (2019-2022). Therefore, there were 64 data samples taken. In addition, the data analysis technique used multiple linear regression. The result showed that capital structure had a positive effect on firm value. On the other hand, firm size had a negative effect on firm value. In contrast, asset growth did not effect firm value.